Methodology and Characteristics of Zad al-Masir fi ‘ilm al-Tafsir by Allama Ibn al-Jawzī - al Azhari, Muhammad Riaz; Safi, Muhammad Safiullah (Journal of Islamic and Religious Studies, 2017)
This article describes the methodology and characteristics of Zad al-masir fi ‘ilm al-tafsir. This is one the finest work of Allama Ibn al-Jawzī, a 6th century prominent Interpreter. Several editions of this Tafsir have been published. However, the edition of dar al-kitab al-‘arbi, Beirut published in four volumes is selected for this study. This exegesis is based on conventional narrations, authentic quotations from the Islamic Scholars and lingual & grammatical discussions. As a witness, causes of verses (asbab al-Nuz┴l), Makki and Madani Surah’s (chapters), the abrogating and abrogated verses (al-nasikh wal-mans┴kh) and Islamic jurisprudence have been discussed in it where needed. The quality of this translation which is admirable is that mostly authentic Ahadith from original sources, and references to well known basic books in relevant discussions have been described.